Low-level laser therapy: A novel therapeutic approach to temporomandibular disorder - A randomized, double-blinded, placebo-controlled trial - R Shobha; Veena S Narayanan; B S Jagadish Pai; H P Jaishankar; M J Jijin (Wolters Kluwer Medknow Publications, 2017)
Aims and Objective: The objective of this study was to assess the effectiveness of low-level laser therapy (LLLT)/low intensity laser therapy (LILT) in the management of temporomandibular joint (TMJ) pain in a random and double-blind research design. Materials and Methods: TMJ pain patients, randomly assigned into two groups: Group 1 (n = 20) and Group 2 (n = 20), received 2-3 treatments per week for 8 sessions of active LILT with diode laser (gallium aluminum arsenide, 810 nm, 0.1 W). Measures of TMJ pain during function were evaluated at baseline, after completion of 8 sessions of laser treatment, and 30 days after the final laser therapy. Results: At the final treatment point, within-group, pain reduction was observed in both active LLLT and placebo groups at day 0 (P = 0.000), 8th session (P = 0.000), and 1 month (P = 0.001). Between the groups, there is no significant difference at day 0 (P = 0.214), 8th session (P = 0.806), and 1 month (P = 0.230). Significant increased mouth opening was observed in both Group 1 and Group 2 (P = 0.006 and P = 0.021, respectively) after treatment. However, no significant difference was found between the two groups (P = 0.330). Furthermore, significant improvement in clicking was recorded before and after treatment both in Group 1 (P = 0.000) and Group 2 (P = 0.001). Conclusion: The study suggests that LLLT is not better than placebo at reducing TMJ pain during function. It may be assumed that a more tailored application of LLLT should be developed to take into account the multifactorial aspect of the disorder.